2017
DOI: 10.1111/jgh.13453
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C burden and care cascade in Australia in the era of interferon‐based treatment

Abstract: The burden of HCV-related liver disease has increased markedly. Although the proportion diagnosed was high, treatment uptake remained low, with no increase over the last 7 years. Reducing the HCV burden in Australia requires scale-up of interferon-free HCV therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
1
68
0
Order By: Relevance
“…29 Another key drawback in surveillance data is the reliance on clinician knowledge -and systematic recording -of patient characteristics, which may not always be complete. These limitations are of particular importance given that the estimated proportion diagnosed in Australia is 62% for HBV 7 and 75% for HCV.…”
Section: Discussionmentioning
confidence: 99%
“…29 Another key drawback in surveillance data is the reliance on clinician knowledge -and systematic recording -of patient characteristics, which may not always be complete. These limitations are of particular importance given that the estimated proportion diagnosed in Australia is 62% for HBV 7 and 75% for HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a robust testing continuum for those accessing screening, BC remains similar to the US, Australia and other countries in initiating treatment (Maier et al, 2016, Viner et al, 2015, Lazarus et al, 2014, Hajarizadeh et al, 2016). We found that a small proportion (15%) of HCV diagnosed individuals initiated HCV treatment by 2012.…”
Section: Discussionmentioning
confidence: 99%
“…We produced estimates for Australia in 2015 using HCV notifications (HCV antibody) data from 1991 to 2015. The chronic HCV prevalence for 2015 was then obtained by summing all notifications since 1991 and adjusting for spontaneous clearance, mortality, emigration, and cure through interferon and DAA treatment …”
Section: Methodsmentioning
confidence: 99%
“…Further, all physicians, including drug and alcohol specialists and general practitioners, were able to prescribe DAA therapies. This unrestricted DAA access programme, an already high diagnosed proportion, and established high‐coverage harm reduction provide the foundation for HCV elimination in Australia. During the first 10 months of access to DAA therapies in 2016, 32 600 people were treated with DAAs for HCV infection (representing ~14% of the population with chronic HCV infection) .…”
Section: Introductionmentioning
confidence: 99%